The zombie gospel : the walking dead and what it means to be human - Strickland, Danielle (Downers Grove : InterVarsity Press, 2017)
The author explores the ways in which the AMC television show, The Walking Dead, can help us think about survival, community, consumerism, social justice, and the resurrection life of Jesus. After all, in the gospel God raises up a new humanity resuscitated and reanimated by the new life of the Holy Spirit.
It's the end of the world as we know it -- Who are you now? -- Fighting the zombie infection -- Surviving the Apocalypse -- A new way to be human -- The longing -- No more priests -- The bravest and most powerful thing you can do -- Babies in the Apocalypse -- Why this could matter.
Includes bibliographical references.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Walking dead (Television program); Walking dead (Television program); Christian life; Theological anthropology -- Christianity; Occultism -- Religious aspects -- Christianity; Zombies -- Miscellanea; Christian life; Occultism -- Religious aspects -- Christianity; Theological anthropology -- Christianity; RELIGION / Christian Theology / Anthropology; Electronic books